Impact of maize expansion on household economy and production systems in northern Lao PDR - Keophosay, Anousith; Viau, J.; Jobard, E.; Castella, J.C. (2011)
For many years, farmers in remote upland areas of northern Laos just produced rice for self consumption. The production surpluses were bartered against other consumption goods or sold in the market to get some cash. Beside, farmers traditionally planted secondary crops on sloping land such as cassava or maize to feed small livestock such as pig, duck, and chicken. At present, upland agriculture is in transition from subsistence to intensified commercialized production. The rapid expansion of hybrid maize crop illustrates this major shift, leading to increased farmers’ income and reduced poverty. However, current maize-based production systems may not be sustainable, neither ecologically nor economically. In 2009 and 2010, we studied the changes in landscapes and livelihood systems triggered by maize expansion in Xiengkhor district in Huaphan province and Kham and Nonghet districts in iengkhouang province. Since 2005, maize had spread in these districts pushed by government policies and investment in infrastructures and pulled by the growing Vietnamese market. The study showed that maize was adopted by all households, independently of their economic status. The landscapes mosaics have gradually homogenize as maize replaced upland rice shifting cultivation system at the bottom of the hill sides and then progressed upwards towards the hill tops. Economic analyzes showed that the rapid expansion of agricultural land devoted to maize was the main source of income increase. In Xiengkhor district, the absence of fallow or fertilization in permanent maize cropping system gradually leads to land degradation (fertility loss and soil erosion) and to yield decline. Farmers are conscious of this downwardtrend but did not find any alternative so far, as the cropping system is still profitable. In the two districts of Xieng Khouang province, the rapid mechanization of land preparation and use of herbicide prefigure the changes that may happen in Xiengkhor district in the coming years. Maize spread had a tremendous impact on the local communities, widening farmer’s differentiation and changing social networks in favor of powerful middlemen and traders. The widespread use of credit for consumption or production and the high variations in commodity prices have changed their economic environment. Farmers adapted their collective rules and negotiated trade arrangements with new stakeholders. New local institutions are emerging. How local farmers cope with these changes will determine to a large extent the future of their livelihood systems.